Facile fabrication of Fe/Fe5C2@N-doped porous carbon as an efficient microwave absorbent with strong and broadband absorption properties at an ultralow filler loading. (30th August 2022) - Jiang, Bo; Yang, Wang; Bai, Hengxuan; Wang, Chaonan; Xu, Chong; Li, Zhengxuan; Yan, Lu; Zhang, Chengxiao; Wu, Ni; Che, Sai; Wang, Xiaobai; Li, Yongfeng
Abstract: The challenge of realizing low filler loading and high-performance microwave absorbing (MA) materials is still an urgent issue to be solved. Herein, porous N-doped carbon wrapped Fe/Fe5 C2 (Fe/Fe5 C2 @NC) nanocomposite is successfully synthesized by a facile one-step calcination of carbon nitride and ferrocene precursors. The magnetic Fe/Fe5 C2 nanoparticles are tightly and uniformly anchored on the wrinkled carbon nanosheets. Abundant of voids exist between the three-dimensional conductive carbon network, which can result in a low density and a strong interfacial polarization relaxation with effect. Based on the double attenuation mechanisms of dielectric loss and magnetic loss, the optimized Fe/Fe5 C2 @NC-800 possesses a minimum reflection loss value reaching −63.1 dB and an effective absorption bandwidth (EAB) as broad as 7.3 GHz with an extremely low filler loading of 4 wt%. The Fe/Fe5 C2 @NC-800 can even achieve a broad EAB within 4.5–18.0 GHz by tuning the absorber thickness in the range of 2.5–5.0 mm, covering nearly 85% of the whole measured frequency band. This work provides new insights for the development of advanced lightweight MA materials, which has wide effective absorption frequency range and strong absorption intensity at low filling levels. Graphical abstract: The lightweight N-doped porous magnetic carbon, composed of crosslinked carbon layers and wrapped magnetic Fe/Fe5 C2 nanoparticles, delivers strong and broadband microwave absorption properties at an ultralow filler loading of 4 wt%, inspiring the development of novel absorbents. Image 1 Highlights: N-doped porous carbon wrapped Fe/Fe5 C2 composites are constructed by a facile one-step calcination method. Evenly dispersed Fe/Fe5 C2 nanoparticles into the carbon nanosheet provide strong magnetic loss ability. This magnetic-dielectric absorbent delivers excellent microwave performances at an ultralow filler loading of 4 wt%. This work offers a new insight in the design of lightweight, strong and broadband microwave absorbers.